Euroopan komission ehdottaman hiilirajamekanismin vaikutuksia Suomessa ja EU: Ssa - Ville Kaitila; Olli-Pekka Kuusela; Tero Kuusi; Johanna Pohjola; Sampo Soimakallio (The Research Institute of the Finnish Economy (ETLA), 2022)
We assess the potential impact of the EU carbon border adjustment mechanism (CBAM) based on the European Commission's proposal presented in 2021. The CBAM products are divided into four categories: cement, fertilizers, iron and steel products, and aluminium products. In terms of production and the value of foreign trade, iron and steel products are by far the largest category, followed by aluminum products. Based on econometric gravity modelling of trade, the impact on EU imports of products covered by the CBAM would be significant. In normal economic conditions, Finland's extra-EU imports of the products would decrease by a total of around a quarter with the proposed CBAM specifications and current carbon pricing. Based on general equilibrium modelling, the effects of the CBAM would be very small for the Finnish aggregate economy. In Finland and other EU countries, the CBAM would benefit directly or indirectly sectors that manufacture products subject to the mechanism. Other industrial sectors, on the other hand, would suffer slightly from the CBAM. The report assesses implications of different ways to implement the CBAM.
Keywords: Q38; 330; Carbon leakage; Carbon border adjustment mechanism; Gravity model; Computable general equilibrium